1965
DOI: 10.1182/blood.v25.1.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Involvement by Leukemia in Children. I. Relationship to Systemic Leukemia and Description of Clinical and Laboratory Manifestations

Abstract: Observations on the course of 59 children who experienced 109 distinct episodes of CNS involvement by leukemia showed that: 1. This complication may be associated with all types of acute and subacute leukemia. 2. There is no single or combination of diagnostic criteria. Manifestations of increased CSF pressure, such as vomiting, headache, and papilledema are the most frequent clinical findings. However, it should be emphasized that CNS involvement may be associated with normal CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…So mostly malignant cells will be found in the CSF, long before rupture of the piaglial-membrane and infiltration of the brain parenchyma occur (Price and Johnson 1973). In 10-50 % of patients with clinical, electrophysiological or pathologic-anatomical evidence of lcukemic infiltration of brain or meninges, blast-cells can not be detected in the CSF (Hyman et al 1965, Fichsel and Schallah 1972, Crosley et al 1978). However, clinical and electroencephalographic signs of CNS-involvernent may occur, when blast infiltration is still confined to the leptomeninx (Hyman et al 1965).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So mostly malignant cells will be found in the CSF, long before rupture of the piaglial-membrane and infiltration of the brain parenchyma occur (Price and Johnson 1973). In 10-50 % of patients with clinical, electrophysiological or pathologic-anatomical evidence of lcukemic infiltration of brain or meninges, blast-cells can not be detected in the CSF (Hyman et al 1965, Fichsel and Schallah 1972, Crosley et al 1978). However, clinical and electroencephalographic signs of CNS-involvernent may occur, when blast infiltration is still confined to the leptomeninx (Hyman et al 1965).…”
Section: Discussionmentioning
confidence: 99%
“…In 10-50 % of patients with clinical, electrophysiological or pathologic-anatomical evidence of lcukemic infiltration of brain or meninges, blast-cells can not be detected in the CSF (Hyman et al 1965, Fichsel and Schallah 1972, Crosley et al 1978). However, clinical and electroencephalographic signs of CNS-involvernent may occur, when blast infiltration is still confined to the leptomeninx (Hyman et al 1965). This is probably due to compression of arachnoideal blood-vessels by dense blast-accumulations (Price and Johnson 1973).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'*) Specific intracranial localizations, confirmed by histology, are rare. 12* 46 In an earlier study we found only 35 Among 17 patients presenting Hodgkin's disease, 15 had neuropsychic symptoms. Seven demonstrated abnormal intracranial images when examined with CAT.…”
Section: Discussionmentioning
confidence: 86%
“…Samples over 1.00 μmol/L should be diluted into the scope of calibration curve (0.05-1.00 μmol/L) using dilution factor 10 , 100 or 1000. Method comparison was performed among modified EMIT assay, LC-MS/MS (liquid chromatography-tandem mass spectrometry) assay and commercial EMIT assay (Hyman et al, 1965).…”
Section: Methodsmentioning
confidence: 99%